Library Information System at SDN 101826 Tuntungan Web-Based - Siregar, Roya; Alvian Putra, Faiz; Sulindawaty (Electronic Integrated Computer Algorithm Journal, 2024)
The development of technology that is so advanced has a real effect on human life. Libraries can also take advantage of this technological advancement, by building a website-based library information system.  The SDN library 101826 still managed manually, this is very inefficient, because in addition to wasting paper, data is inaccurate, archiving is not neatly organized and messy. When employees want to find borrowed books, they have to check and search manually. It is very draining of energy and time, because many books are lost because it is not known who the borrower of the book is. Based on these problems, the author provides a solution by building a library information system at the elementary school based on the web. Data collection methods include observation, interviews, and literature studies. Meanwhile, the system development method uses Waterfall, and in its design utilizes Unified Modeling Language. The programming language used in coding is PHP with MySQL database. This research requires a library information system that can help library officers in carrying out their activities. The system that has been built can speed up, make it easier and more efficient for visitors in the book search process.